THE EFFECT OF PRICE ON PURCHASE DECISION WITH SERVICE QUALITY AS AN INTERVENING VARIABLE (CASE STUDY ON AMERICAN MEDICAL HEALTH AND SHOP STORE) - Bob Feinberg; Ian Wooton (PT. Radja Intercontinental Publishing, 2020)
In this study, the population was American Medical Health and Shop Store, namely 40 people. Because the target population is less than 100, the sampling technique used is the census method, in which the entire population, totaling 60 Customers of American Medical Health and Shop Store. The results of the first hypothesis research are accepted, meaning that the price variable (X) has a positive and significant effect on service quality (Y1). the second hypothesis is accepted, meaning that price (X) has no significant effect on purchasing decisions (Y2). the third hypothesis is accepted, meaning that Service Quality (Y1) has a positive and significant effect on Purchase Decision (Y2).